Determinación del uso consuntivo del cultivo de fréjol (Phaseolus vulgaris L.), variedad ICA Quimbaya; utilizando el lisímetro de pesaje en la granja experimental La Argelia, Loja - Rodríguez Soto, José Luis (2014)
A relatively inexpensive weighing lysimeter (FELT 6), was acquired by the Department of Agricultural Irrigation of the Area of Renewable Natural Resources. It was installed in order to verify its functionality and to measure the potential evapotranspiration (pET). A total of 24 packaging containers were used as ground receivers; culturing them with beans (Phaseolus vulgaris L.) under these receivers, plastic pots were placed to collect drainage. As a result of the experiment, the weighing lysitemer depicted simple and easy usage but unreliability in the measurements. An average ETc value of 3,59 mm/day was found during the vegetative cycle of the culture.